Experimental heat transfer and flow simulations of rectangular channel with twisted-tape pin-fin array. (February 2021) - Chang, S.W.; Wu, P.-S.; Cai, W.L.; Yu, C.H.
Highlights: The flow and heat transfer of a channel with a twisted-tape pin-fin array were studied. The multiple vortical flows induced by the twisted-tape pin-fin array increased the heat transfer rate. The Nu value of the designed channel was 5.26–4.73 times higher than that of a plain tube. The TPF value of the designed channel was 1.55–1.39 times higher than that of the plain tube. The Nu and f correlations of the designed channel were determined. Abstract: In this study, an innovative twisted-tape pin-fin array was proposed for passive heat transfer enhancement (HTE) to improve the aerothermal performance of channel flows. The full-field Nusselt number distributions, Fanning friction coefficients and thermal performance factors of an improved channel were measured at Reynolds numbers of 5000, 7500, 10, 000, 12, 500, and 15, 000. The turbulent channel flows were numerically explored using the ANSYS-Fluent code to perform correlative analysis between the aerothermal measurements and numerical flow results. A set of aerothermal data and numerical flow results was selected to illustrate the properties of HTE and the responsive flow mechanisms. Because of the vortical flows induced by each twisted tape in the array, the average measured Nusselt numbers and Fanning friction coefficients of the improved channel were 5.26–4.73 and 39.4–38.5 times higher than those of a plain tube, respectively; thus, the thermal performance factor (TPF) of the improved channel was 1.55–1.39 when 5000 < Re < 15, 000. Compared with the pin-fin channels with different geometries reported in the literature, the twisted-tape pin-fin channel designed in this study provided a higher degree of HTE and thus a higher TPF at the same pressure drop penalty and pumping power. On the basis of the experimental results, two empirical correlations that were used to evaluate the average endwall Nusselt number and Fanning friction coefficient of the designed pin-fin channel were proposed for relevant applications.